Acute Pericoronitis - Engpaiboon, Jantarat (Journal of Health Science of Thailand, 1992)
Acute pericoronitis is a painful, debilitating infection of the operculum overlying an erupting or semi – impacted tooth that is most commonly found among young adult. The tooth at highest risk for acute pericoronitis is a fully erupted vertical mandibular third molar that is contact with the adjacent second molar, at or above the occlusal plane, and partially encapsulated by soft or hard tissue. Because of the dangers with acute pericoronitis, prophylactic extraction of third molars at high risk has been recommended.